A modern creative teacher - Cieśleńska, Beata (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
Modern reality, in which we exist, is based on many innovative models. They can be observed in school environment in particular. In a Polish school a person who points changes and innovations in the right direction is a teacher. His/her aiming for originality and freedom to act translates into creative activity. The sign of this creativity are such features as: higher than average spontaneity and expressiveness, courage, sense of humour, activity and determination in achieving set goals. The school ceases to be the place in which creativity is limited only to talented individuals. Teachers working there are obliged to suport abilities to create new and valuable products, as well as innovative and creative actions of all students. Who is a modern creative teacher then? The literature presents him/her as a person desiring changes and diversity at the same time. A creative teacher is a creative man, taking intellectual risk and looking outwards. When looking for a teacher who would cope with modern expectations, not only a person who teaches but a man of dialogue and innovation, we look for a master of teaching and education, which is a creative teacher. We look for a pedagogue who inspires to learn and think over the schedule, fights for a student and his/her originality.